2021
DOI: 10.3389/fcell.2021.764313
|View full text |Cite
|
Sign up to set email alerts
|

Novel Implications of MicroRNAs, Long Non-coding RNAs and Circular RNAs in Drug Resistance of Esophageal Cancer

Abstract: Esophageal cancer is the eighth most common malignancy and the sixth leading cause of cancer-related deaths worldwide. Chemotherapy based on platinum drugs, 5-fluorouracil, adriamycin, paclitaxel, gemcitabine, and vinorelbine, as well as targeted treatment and immunotherapy with immune checkpoint inhibitors improved the prognosis in a portion of patients with advanced esophageal cancer. Unfortunately, a number of esophageal cancer patients develop drug resistance, resulting in poor outcomes. Multiple mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…Furthermore, epigenetics and non-coding RNAs play a critical role in EC-related multidrug resistance and affect the effectiveness of therapies. In fact, EC’s susceptibility to recurrence, metastasis, and drug resistance development after first-line treatment, highlights the urgent requirement for optimizing the medicine regimen ( Liu et al, 2021 ; Wei et al, 2021 ).…”
Section: Current Gastrointestinal Cancers Therapies Challenges and Li...mentioning
confidence: 99%
“…Furthermore, epigenetics and non-coding RNAs play a critical role in EC-related multidrug resistance and affect the effectiveness of therapies. In fact, EC’s susceptibility to recurrence, metastasis, and drug resistance development after first-line treatment, highlights the urgent requirement for optimizing the medicine regimen ( Liu et al, 2021 ; Wei et al, 2021 ).…”
Section: Current Gastrointestinal Cancers Therapies Challenges and Li...mentioning
confidence: 99%
“…Albeit the mechanisms of platinum drug resistance have been the subject of numerous investigations, few efficient, targeted treatments are available ( 200 202 ). Mounting evidence suggests that circRNAs are involved in multiple cellular processes and malignancies, including ESCC ( 203 , 204 ). Understanding the underlying causes of chemoresistance is crucial for developing effective ESCC treatments and preventing recurrence.…”
Section: Clinical Application Of Circrna In Esccmentioning
confidence: 99%
“…Nonetheless, chemotherapy resistance is still the biggest factor limiting the clinical application of 5-FU in EC, and its molecular mechanism is complex and changeable 21 . Accumulating evidence has shown that lncRNA is becoming a star molecule affecting tumor chemotherapy 22 , 23 . Similarly, many articles verify the critical effect of lncRNA on 5-FU sensitivity in EC 24 26 .…”
Section: Introductionmentioning
confidence: 99%